A neuroglia-based interpretation of glaucomatous neuroretinal rim thinning in the optic nerve head. (July 2020) - Lee, Eun Jung; Han, Jong Chul; Park, Do Young; Kee, Changwon
Abstract: Neuroretinal rim thinning (NRR) is a characteristic glaucomatous optic disc change. However, the precise mechanism of the rim thinning has not been completely elucidated. This review focuses on the structural role of the glioarchitecture in the formation of the glaucomatous NRR thinning. The NRR is a glia-framed structure, with honeycomb geometry and mechanically reinforced astrocyte processes along the transverse plane. When neural damage selectively involves the neuron and spares the glia, the gross structure of the tissue is preserved. The disorganization and loss of the glioarchitecture are the two hallmarks of optic nerve head (ONH) remodeling in glaucoma that leads to the thinning of NRR tissue upon axonal loss. This is in contrast to most non-glaucomatous optic neuropathies with optic disc pallor where hypertrophy of the glioarchitecture is associated with the seemingly absent optic disc cupping. Arteritic anterior ischemic optic neuropathy is an exception where pan-necrosis of ONH tissue leads to NRR thinning. Milder ischemia indicates selective neuronal loss that spares glia in non-arteritic anterior ischemic optic neuropathy. The biological reason is the heterogeneous glial response determined by the site, type, and severity of the injury. The neuroglial interpretation explains how the cellular changes underlie the clinical findings. Updated understandings on glial responses illustrate the mechanical, microenvironmental, and microglial modulation of activated astrocytes in glaucoma. Findings relevant to the possible mechanism of the astrocyte death in advanced glaucoma are also emerging. Ultimately, a better understanding of glaucomatous glial response may lead to glia-targeting neuroprotection in the future. Graphical abstract: Image 1 Highlights: The NRR is a "glia-framed" structure with a transverse honeycomb organization. Disorganization/loss of the ONH glioarchitecture allows NRR tissue thinning in glaucoma. NRR with pallor shows hypertrophic gliosis with preserved architecture. Mechanical and biological microenvironments may induce the eventual glial loss. Relevant glial-targeting neuroprotection may be considered.